Effect of processing parameters on nanofibers via water vortex electrospinning: article - Mohd Izhar, Muhammad Haziq; Kadri, Atikah (2017)
Electrospinning is recognized to be flexible process which able to produce fibers made of any compositions with desired diameter from microns to several nanometers. Many methods have been developed for improvement and to overcome the limitations regarding the produced fibers. In this work, water vortex was used as one of the method to produce nanofibers in form of a yarn. The aim of this work was to produce nanofibers from water vortex electrospinning technique. The morphological structure for the produced fibers were characterized using scanning electron microscope (SEM). The structures of the produced fiber were analyzed.